The association between macronutrients and severe musculoskeletal pain in the Tromsø7 study - Hashim, Sara (UiT Norges arktiske universitet, 2023)
Musculoskeletal pain is a widespread health issue that affects millions of people worldwide. It refers to any chronic or acute pain that affects muscles, ligaments, bones, and tendons. The most common types of musculoskeletal pain are low back and neck pain, with low back pain being the primary cause of disability globally. People who experience musculoskeletal pain often face negative consequences, such as increased use of medication, time off work, financial strain, and reduced quality of life. Therefore, there is a need for new non-pharmaceutical approaches to manage severe pain. Recent studies indicate a potential link between chronic pain and nutrient intake. This study aimed to investigate the relationship between macronutrients and severe musculoskeletal pain in the Tromsø population.